The Effect of Distance to Colleges on Application Behavior - Judith M. Delaney; Paul J. Devereux (Institute of Labor Economics (IZA), 2024)
We find substantial differences in college applications for students who have equal college opportunities and prior achievement but vary in distance to the nearest selective and non- selective college. Students who live closer to a selective college are more likely to list prestigious programs and colleges as their top choice. This results in differences in enrollment outcomes with the largest associations for those in the middle of the achievement distribution.
Keywords: I21; I23; I24; 330; distance; college application; college enrollment; test score